Integrating Motivational Interviewing and Cognitive Behavioral Therapy for Addressing Violent Behavior in Secondary School Students: A Stages-to-Change Intervention Module - Man, Emilia; Mohamed, Mohammad Aziz Shah; Jusoh, Ahmad Jazimin; Hassan, Noor Asiah (International Journal of Education, Information Technology, and Others, 2023)
The rise in disciplinary issues among school students has become a cause for concern with challenges in managing and curbing negative activities. Employing counselling interventions, particularly the 'Brief Therapy' approach has proven effective in addressing student misbehaviour. This study proposes the development of a counselling intervention module to specifically tackle promiscuous behaviour among high school students. The module integrates Motivational Interviewing, based on the Trans theoretical Model and Stages of Change. Additionally, Cognitive Behaviour Therapy complements Motivational Interviewing to expedite the treatment process. The module construction follows a two-level, nine-step framework. The study aims to deepen understanding of behaviour change processes, ultimately reducing disruptive behaviour. Special attention and mastery of this new approach by counsellors and practitioners are crucial. Moreover, aligning with the Malaysian Education Development Plan 2013-2025 (PPPM), the study contributes to strategic planning in schools, emphasizing the development of students' potential.